REFORMULATION OF TAX AND CYBER LAW: TOWARDS INTELLECTUAL PROPERTY-FRIENDLY DIGITAL TRANSACTION OVERSIGHT - Irwansyah Tanjung; Misnan Al-Jawi (PT. Radja Intercontinental Publishing, 2026)
This study analyzes the legal tension between data extraction authority within digital tax oversight in Indonesia and taxpayers' rights to trade secret protection. The implementation of the Core Tax Administration System (Coretax) and the Artificial Intelligence Compliance System (AICEco) proses risks of disclosing technological data and internal corporate financial information due to the absence of comprehensive technical regulations. Employing a normative legal research method coupled with a comparative approach, this study examines the tax and cyber legal frameworks in the United States, Germany, and Australia. The findings indicate that regulations in Indonesia lack integration regarding digital evidence management compared to the United States, which implements protective orders, and Germany, which aligns fiscal audits with the boundaries of the General Data Protection Regulation (GDPR). This study recommends the reformulation of national tax policy, encompassing the institutionalization of the Tax Control Framework (TCF), the adoption of protective order provisions within tax court procedural law, encryption standardization in third-party partnership system sandboxing, and the optimization of the dominus litis principle by the Public Prosecution Service to guarantee legal certainty and the protection of taxpayers' intellectual property rights.